Empowering Indonesia's Local Brands: A Case Study on Ruaya’s Digital Branding and Marketing - Herfini, Dewi Diastuti; Iranti, Tasya Putri; Nadhifah, Yassela Luqi (COMMENTATE: Journal of Communication Management, 2024)
This study highlights how Public Relations (PR) practitioners assist Indonesia's local Micro, Small, and Medium Enterprises (MSMEs) in the souvenir printing business for various needs. The products created by the local MSME named Ruaya are used by their clients to design digital campaigns aimed at developing better branding strategies and increasing customer awareness in marketing efforts. "The research focuses on two main issues: integrating the Cognitive Dissonance Theory (CDT) into Ruaya’s product branding and promotion, and developing strategies for employee training and leadership as the company transitions from traditional to digital media for branding and promotion." The aim of this paper is to develop strategies that Ruaya can adopt to effectively utilize social media for creating branding strategies that enhance brand awareness and attract new consumers. Additionally, the research focuses on building employee capacity by leveraging CDT as a communication tool to promote active online engagement, adopting niche marketing strategies, and establishing a unique identity for Ruaya. The strategies suggested by PR practitioners to Ruaya’s management include consistently creating video content with storytelling elements, planning content regularly, and collaborating with influencers. The novelty of this qualitative research lies in the exploration of CDT utilization, highlighting its role in three aspects: leadership, marketing, and content strategy.